Relationship between urban green space and mental health in older adults: mediating role of relative deprivation, physical activity, and social trust - Zuo, Wen; Cheng, Bin; Feng, Xinyan; Zhuang, Xuefang (Frontiers in Public Health, 2024)
Introduction The importance of improving older adults' mental health is increasing worldwide with the rapid development of the aging process. Green space is an important part of the urban built environment, demonstrates a deep connection with the mental health of older adults, and its internal mechanisms have been widely studied. This study analyzed the influence of urban green spaces on the mental health of older adults via three factors: relative deprivation, physical activity, and social trust. Methods Based on the 2018 China Labor Dynamics Survey, a multi-level structural equation model was used to explore the mediating roles of relative deprivation, physical activity, social trust in urban green spaces, and the mental health of older adults. Results Urban green space was positively correlated with the mental health of older adults. Relative deprivation and physical activities played a mediating role between urban green space and the mental health of older adults. Discussion An increase in urban green spaces can help increase the number of older adults obtaining green space resources, and help them maintain good mental health. Secondly, older adults with a relatively homogeneous environment have more equal opportunities to obtain urban green space resources, which helps to reduce the comparison of older adults in access to green space resources and reduce the adverse impact of relative deprivation on their mental health. Additionally, increasing urban green spaces can encourage older adults to engage in physical activities and improve their mental health. Finally, we suggest improving the accessibility, fairness, and quality of green spaces, paying attention to the psychological needs of older adults, encouraging older adults to engage in physical activities in green spaces, and taking various measures to enhance the positive role of green space on the mental health of older adults.